Pemikiran Filosofi Mulla Sadra - Juwaini Juwaini (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2013)
Mulla Shadra as famous intellectual figure, its opinion attend to show the intellectual tradition reality which is stayed alive and rapidly grow in Persian. Opinion of Mulla Shadra about Hikmah Muta'aliyah tread on to philosophic approach which aim to explain the nucleus; core, reality, or hikmah of concerning something that reside in to return the its formal object. Philosophic approach conducted is to explain what at the opposite of something tangible. With the this philosophic approach study, all thinker or doctrine from Muhammadan philosophy will be able to give the meaning to something in its life experience and can take the hikmah to be made a new invention. Philosophic approach representing study of Mulla Shadra is Hikmah Muta'aliyah. In this study there is three elementary principle of epistemologi that is: intellectual intuition, rational verification and syariat, so that according to Mulla Shadra, hikmah represent the wisdom which is earned by spiritual clarification, explained by Mulla Shadra in the form of and rational argument, and realized by according to order syariat. Meanwhile, from side ontologis, Hikmah Muta'aliyah based for three things, principal exist, gradation exist, and move substansial